2011
DOI: 10.1016/j.crvi.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of female preference for male size predicts subsequent choice of spawning partner in a socially monogamous cichlid fish

Abstract: Rapid assessment of female preference for male size predicts subsequent choice of spawning partner in a socially monogamous cichlid fish L'e´valuation rapide de la pre´fe´rence des femelles pour la taille des ma ˆles permet de pre´dire le choix d'un partenaire de ponte chez un poisson cichlide´socialement monogame Franc ¸ois-Xavier Dechaume-Moncharmont a, *, Je ´re ´mie H. Cornuau a , Ismae ¨l Keddar a , Malika Ihle a , Se ´bastien Motreuil a , Frank Ce ´zilly a,b

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…1c) to test for the female's mating preference (e.g. Thünken et al 2007;Dechaume-Moncharmont et al 2011). After a 10-min acclimatisation period, the female was allowed to choose between the two stimulus males during a 22-min mate choice phase that was divided into two recording periods of 11 min each.…”
Section: Mate Choice Trialsmentioning
confidence: 99%
“…1c) to test for the female's mating preference (e.g. Thünken et al 2007;Dechaume-Moncharmont et al 2011). After a 10-min acclimatisation period, the female was allowed to choose between the two stimulus males during a 22-min mate choice phase that was divided into two recording periods of 11 min each.…”
Section: Mate Choice Trialsmentioning
confidence: 99%
“…It has been used for studies on small teleosts for evaluating the effects of sedative shipping additives under industrial conditions (Kilgore et al, 2009). Amatitlania nigrofasciata has also been frequently used in fish behaviour studies (Arnott et al, 2011;Dechaume-Moncharmont et al, 2011;Moscicki et al, 2011;Chee et al, 2012;van Breukelen, 2013). In one behaviour study, social stress was reported to be associated with gallbladder hypertrophy and increased bile retention (Earley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments revealed that males and females of P. taeniatus use body size (an ornamental trait) as well as genetic relatedness (a compatibility criterion) in mate choice, when these criteria were tested independently from each other: as in other cichlids [33][34][35][36][37], both sexes preferred large individuals [32]. Mating with large individuals provides several indirect and direct benefits in biparental cichlids, e.g.…”
Section: Introductionmentioning
confidence: 99%